Children with two homes: Psychological problems in relation to living arrangements in Nordic 2- to 9-year-olds. Issue 2 (March 2019) - Bergström, Malin; Fransson, Emma; Wells, Michael B.; Köhler, Lennart; Hjern, Anders
Aim: Joint physical custody, children spending equal time in each parents' respective home after a parental divorce, is particularly common in Nordic compared with other Western countries. Older children have been shown to fare well in this practice but for young children there are few existing studies. The aim of this paper is to study psychological problems in 2- to 9-year-old Nordic children in different family forms. Methods: Total symptom score according to the Strengths and Difficulties Questionnaire as well as scores showing externalizing problems were compared among 152 children in joint physical custody, 303 in single care and 3207 in nuclear families through multiple linear regression analyses. Results: Children in single care had more psychological symptoms than those in joint physical custody (B = 1.08; 95% CI 0.48 to 1.67) and those in nuclear families had the least reported symptoms (B = −0.53; 95% CI −0.89 to −0.17). Externalizing problems were also lower in nuclear families (B = −0.28, 95% CI −0.52 to −0.04) compared with joint physical custody after adjusting for covariates. Conclusions: Young children with non-cohabiting parents suffered from more psychological problems than those in intact families. Children in joint physical custody had a lower total problem score than those in single care after adjusting for covariates. Longitudinal studies with information on family factors before the separation are needed to inform policy of young children's post-separation living arrangements .